Ownership Strategies and Survival of Foreign Subsidiaries: Impacts of Institutional Distance and Experience - Gaur, Ajai S.; Lu, Jane W. (Journal of Management, 2007)
This article integrates institutional theory and organizational learning perspective and proposes a contingency framework on the relationship between ownership strategies and subsidiary performance. Using a sample of Japanese subsidiaries worldwide, the article finds important main effects of ownership, institutional distance, and host country experience on subsidiary survival. Furthermore, the effect of ownership is contingent on institutional distance and host country experience. In institutionally distant countries, subsidiaries have better survival chances if foreign parents have more ownership. Host country experience has a negative impact on subsidiary survival, but the effect is weaker if foreign parents have larger ownership positions in the subsidiaries.